1.) m + n = 5
m - 3 = n
m + m - 3 = 5
2m - 3 = 5
2m = 8
m = 4
m + n = 5
4 + n = 5
n = 1
Therefore m =4 and n =1
2.) I don't think this one can be done because:
6x - 2(3x - 7) = 12
6x - 6x + 14 = 12
0x + 14 = 12
0x = - 2
3.) 5x + 2(x + 7) = 7
5x + 2x + 14 = 7
7x + 14 = 7
7x = - 7
x = - 1
y = x + 7
y = - 1 +7
y = 6
Therefore x = - 1 and y = 6
4.) I don't think this one can be done either because:
14 - 4x = 2y
Is the same as:
7 - 2x = y
Which is the same as the first equation. You then get 0x because if you substitute y in:
7 - 2x + 2x =7
7 = 7
5.) y = 4x + 6
5x - 4x + 6 = 6
x +6 = 6
x = 0
y = 4x + 6
y = (4x0) + 6
y = 6
Therefore x = 0 and y = 6